Phenolic Compounds Reduce the Fat Content in Caenorhabditis elegans by Affecting Lipogenesis, Lipolysis, and Different Stress Responses - Paula Aranaz; David Navarro-Herrera; María Zabala; Ana Romo-Hualde; Miguel López-Yoldi; José Luis Vizmanos; Fermín I. Milagro; Carlos J. González-Navarro (MDPI AG, 2020)
Supplementation with bioactive compounds capable of regulating energy homeostasis is a promising strategy to manage obesity. Here, we have screened the ability of different phenolic compounds (myricetin, kaempferol, naringin, hesperidin, apigenin, luteolin, resveratrol, curcumin, and epicatechin) and phenolic acids (p-coumaric, ellagic, ferulic, gallic, and vanillic acids) regulating C. elegans fat accumulation. Resveratrol exhibited the strongest lipid-reducing activity, which was accompanied by the improvement of lifespan, oxidative stress, and aging, without affecting worm development. Whole-genome expression microarrays demonstrated that resveratrol affected fat mobilization, fatty acid metabolism, and unfolded protein response of the endoplasmic reticulum (UPRER), mimicking the response to calorie restriction. Apigenin induced the oxidative stress response and lipid mobilization, while vanillic acid affected the unfolded-protein response in ER. In summary, our data demonstrates that phenolic compounds exert a lipid-reducing activity in C. elegans through different biological processes and signaling pathways, including those related with lipid mobilization and fatty acid metabolism, oxidative stress, aging, and UPR-ER response. These findings open the door to the possibility of combining them in order to achieve complementary activity against obesity-related disorders.